2010
DOI: 10.1111/j.1532-7795.2010.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Hurts: The Academic, Psychological, and Physical Well-Being of Adolescents

Abstract: Little is known about the frequency of ethnic or racial discrimination and its implications for Latin American and Asian youths' development. In this study, we examined if there were ethnic and generation differences among 601 12th graders from Latin American (36%), Asian (43%), and European (19%) backgrounds in the frequency of peer, adult, and daily discrimination, and whether discrimination predicted their well-being. Adolescents from Latin American and Asian backgrounds reported more adult and peer discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
264
7
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(310 citation statements)
references
References 81 publications
27
264
7
12
Order By: Relevance
“…Consistent with previous research, young men reported more perceived discrimination than young women, possibly because men are stereotyped as dangerous and threatening (Greene et al 2006;Huynh and Fuligni 2010). However, men and women had similar perceptions of societal devaluation, suggesting that although men and women experience different frequencies of personal perceived discrimination, both genders are aware of the society's views and perceptions of their ethnic group.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with previous research, young men reported more perceived discrimination than young women, possibly because men are stereotyped as dangerous and threatening (Greene et al 2006;Huynh and Fuligni 2010). However, men and women had similar perceptions of societal devaluation, suggesting that although men and women experience different frequencies of personal perceived discrimination, both genders are aware of the society's views and perceptions of their ethnic group.…”
Section: Discussionsupporting
confidence: 88%
“…Among adolescents, perceived discrimination consistently is associated most with psychological adjustment, including anxiety, depression, self-esteem, physical symptoms, delinquency, drug use, and distress (Fisher et al 2000;Gibbons et al 2007;Greene et al 2006;Huynh and Fuligni 2010;Samaniego and Gonzales 1999). Among Asian American and Latino college students, perceived discrimination is associated with higher psychological distress, suicidal ideation, state anxiety, trait anxiety, and depression (Hwang and Goto 2009).…”
Section: Associations With Adjustmentmentioning
confidence: 94%
See 1 more Smart Citation
“…28, nº 3 (octubre) tigated (Berkel et al, 2010;Green, Way, & Pahl, 2006;Grossman & Liang, 2008;Huynh & Fuligni, 2010;Liebkind & Jasinskaja-Lahti, 2000;Oppedal, 2011. However, immigrant children and youth may also experience other contextual challenges both within their ethnic in-group networks and during social interaction with out-group majority peers (Lay & Nguyen, 1998;Vinokurov, Trickett, & Birman, 2002).…”
Section: Acculturation Risk Factorsmentioning
confidence: 99%
“…Referring to grades via academic achievement in their analyses, Alva and de los Reyes (1999) report that academic achievement was negatively correlated to acculturative stress and that the effects of the stress were not attenuated by a student's perceived self-competence. Likewise, Huynh, and Fuligni (2010) find that when compared to their white and Asian peers, Latino high school students showed lower levels of school achievement as the result of higher levels of stress.…”
Section: Gradesmentioning
confidence: 96%